(untitled) (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Increasing scientific publications is an indicator that shows the teacher’s ability to write down his thoughts and disseminate scientific activities that have been carried out. Currently, the average SMA Negeri 1 Pamboang Majene has never participated in scientific article writing training activities, so partners need scientific article training to increase teacher professionalism, especially at State High School. 1 Pamboang Majene. The PKMM team collaborated with SMA Negeri 1 Pamboang Majene to conduct training and mentoring for SMA Negeri 1 Pamboang teachers. This activity was carried out in October 2022-January 2023. This activity was attended by 29 participants from SMA Negeri 1 Pamboang Majene offline. The title of the workshop activity was themed "Scientific Article Writing Training to Increase the Professionalism of Teachers of SMA Negeri 1 Pamboang, Majene." Based on the results of the evaluation carried out, it is known that the material presented is important and useful material as well as the need for teachers to improve teacher professionalism in these schools.